Biomechanical analysis for the IAAF World Championships London 2017 400 m Women's - Pollitt, L.; Walker, J.; Tucker, C.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
In the highly anticipated women`s 400 m final on the evening of Wednesday 9th August, Phyllis Francis upset the form book and secured one of the surprise gold medals of the championships with a lifetime best performance despite poor weather conditions. In similar circumstances to the 2016 Olympic final, Shaunae Miller-Uibo led the defending champion Allyson Felix into the home straight. Although Felix could not produce her trademark finish and began to run out of steam, it was Miller-Uibo who faltered 30 m from the line eventually finishing fourth in 50.49 s. Francis took full advantage, passing Felix at 370 m and then the stricken Miller-Uibo at 380 m to secure gold in 49.92 s. Silver went to the impressive 19-year-old Bahraini Salwa Eid Naser. The time of 50.06 s surpassed her lifetime best performance during the semi-finals (50.08 s) where she again overtook Felix in the closing stages. Felix did however take the bronze in a time of 50.08 s, and at the same time equalled the record of the most successful athletes at the World Championships, alongside Usain Bolt and Merlene Ottey.